PERANAN KELOMPOK INFORMASI MASYARAKAT(KIM) KAMPUNG PURUN DI KELURAHAN PALAM KECAMATAN CEMPAKA KOTA BANJARBARU - Herry Isdaryoko; Anhar Yani; Mukhlan Khairiry; Rizalul Gadi; Septeria Noor Yuliannisa (Administraus, 2022)
Abstract : The research has the following objectives to determine: (1) the role of the Purun Village Community Information Group (KIM) in increasing the income of the Purun craftsmen, (2) the constraints on the role of the Purun Village Community Information Group (KIM) in increasing the income of the Purun craftsmen, (2) the solutions in overcome the constraints of the role of the Community Information Group (KIM) of Kampung Purun in increasing the income of Purun craftsmen. This research uses a descriptive qualitative research form. Researchers used data collection techniques Interview, Observation, and Documentation. The results of the research show: (1) The role of the Community Information Group (KIM) of Kampung Purun in increasing the income of Purun craftsmen is an effort that can be a connector for delivering information to the community. In the role of the Community Information Group (KIM) of Kampung Purun, it is stated in the Regulation of the Minister of Communication and Information No. 8/ Per/ M. Kominfo/6/ 2010 concerning Development and Empowerment of Social Communication Institutions. Community information groups including the Community Information Group (KIM) of Kampung Purun in increasing the income of Purun craftsmen, (2) Constraints on the role of the Community Information Group (KIM) of Purun Village in increasing the income of Purun craftsmen regarding aspects of the lack of quality of craftsmen, availability of marketing channels and available for business development, and (3) constraints on the role of the Purun Village Community Information Group (KIM) in increasing the income of purun craftsmen by improving the quality of craftsmen/HR in each business field, increasing funding independently, and building Keywords: Community Information Group, Income, Purun craftsmen Abstrak : Penelitian memiliki tujuan sebagai berikut untuk mengetahui : (1) peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun, (2) kendala peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun, (2) solusi dalam mengatasi kendala peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun. Penelitian ini menggunakan bentuk penelitian Deskriptif Kualitatif. Peneliti menggunakan teknik pengumpulan data Wawancara, Observasi, dan Dokumentasi. Hasil penelitian menunjukan : (1) Peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun merupakan upaya yang dapat menjadi penyambung penyampaian informasi kepada masyarakat. Dalam peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun ini tercantum pada Peraturan Menteri Komunikasi dan Informatika No.8/Per/M.Kominfo/6/2010 tentang Pengembangan dan Pemberdayaan Lembaga Komunikasi Sosial. Kelompok informasi Masyarakat termasuk Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun, (2) Kendala peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun menyangkut aspek kurangnya kualitas pengrajin, ketersediaan saluran pemasaran serta dan yang tersedia untuk pengembangan usaha, dan (3) Kendala peranan Kelompok Informasi Masyarakat (KIM) Kampung Purun dalam meningkatkan pendapatan pengrajin purun dengan meningkatkan kualitas Pengrajin/SDM pada masing-masing bidang usaha, Menambah pendanaan secara swadaya, serta membangun. Kata Kunci: Kelompok Informasi Masyarakat, Pendapatan, Pengrajin Purun